Hydroxyapatite-based catalysts derived from food waste digestate for efficient glucose isomerization to fructose - Raffel Dharma Patria (KeAi Communications Co. Ltd., 2021)
Transforming biomass waste into cost-effective catalysts for chemical reactions provides new opportunity for biomass waste valorization. In this work, we examined the possibility of using food waste solid digestate as raw materials for the production of a heterogeneous catalyst for glucose isomerization to fructose, which is one of the important intermediates for the production of platform chemicals, hydrocarbon fuels and synthetic materials from biomass. Hydroxyapatite-based catalysts were obtained from food waste digestate by a coupled hydrothermal-calcination approach. In the hydrothermal treatment process, the addition of exogenous calcium can adjust the alkalinity of the catalyst, which is beneficial to improve the activity of the catalyst. The reaction parameters such as reaction temperature, reaction time and catalyst dosage have also been optimized. The catalyst showed excellent catalytic performance in the glucose isomerization reaction resulting in a high fructose yield of 32.3% with a reaction time of only 20 ​min at 80 ​°C in water. The catalyst can be reused after a simple regeneration without significant activity. This work provides a win-win strategy, which not only solves the problem of the disposal and utilization of digestate, but also expands the synthesis method of the glucose isomerization reaction catalyst.